Ice Fluctuations In Moraine Canyon, Antarctica Dated With Cosmogenic 26Al, 10Be, And 21Ne - Lord, Emma Mirabelli (UND Scholarly Commons, 2016)
Knowledge and understanding of past Antarctic ice sheet behavior is necessary to illustrate ice sheet response to our currently warming climate and the ice sheet’s contribution to global sea level change. Our knowledge of glacial fluctuations in the southern Transantarctic Mountains (TAM) is limited because few studies in this area have been done; therefore much information can be gained from further investigations in this region. Glacial deposits in Moraine Canyon, a tributary of Amundsen Glacier in the southern TAM, show numerous periods of ice thickening. Moraine Canyon responds to changes in the thickness of Amundsen Glacier, and Amundsen Glacier responds to changes in thickness of the East Antarctic and West Antarctic Ice Sheets (EAIS and WAIS). 10Be, 26Al, and 21Ne concentrations from vertical profiles in ~1m deep soil pits from four glacial deposits provide exposure ages and local regolith erosion rates. Exposure ages from three lateral moraines and one valley floor deposit show an overall decrease in ice levels in Moraine Canyon since at least 1.21 Ma punctuated by at least four periods of ice thickening of Amundsen Glacier. Local regolith erosion rates range from 0.21-4.40 m Ma-1. During subsequent periods of ice thickening, lateral moraines were deposited at 1.21 Ma, 1.10 Ma, and 80.4 ka. The regolith overlying glacial ice on the valley floor was deposited 287 ka. A period of significant ice thinning in Moraine Canyon occurred between 1.10 Ma and 287 ka. During this thinning event, ice levels of Amundsen Glacier were low enough to allow the glacial ice in Moraine Canyon to completely flow out of the valley. Significant thinning of the EAIS at the head of Amundsen Glacier was necessary for this amount of ice lowering to occur during this time. This research provides new constraints on past fluctuations of the EAIS and suggests that it is more sensitive to shorter term climatic fluctuations than previously thought.